HISTÓRIAS CONTADAS NAS ENTRELINHAS: ética e moral nas fábulas de La Fontaine e nos contos de fadas de Charles Perrault e a relação com a educação e a infância - Teixeira, Bárbara Portilho (2023)
Literature has been present since the discovery of writing and has driven societies, correlating its own history with the evolutionary processes of education. Thus, the philosophy carried by great virtues allows still impermeable views of human characteristics. This dissertation research starts from the following investigative questions: are there ethical and moral issues between the lines of fables and fairy tales? Are fables and fairy tales suitable for early childhood education? The study, of a basic nature, is part of the Research Line “History and Historiography of Education” of the Postgraduate Program at the Federal University of Uberlândia, using a qualitative approach that highlights exploratory, descriptive, explanatory, and bibliographic research. The general objective of this dissertation is to analyze some of La Fontaine’s fables in “Selected Fables” (1668) and some of Perrault’s fairy tales in the collection “Mother Goose Tales” (1697) concerning moral and ethical values, engaging in some reflections on children’s literature and its historical, educational, social, and cultural approaches. As for the specific objectives, they aim to report the historical process of children’s literature, discuss the pertinence of fairy tales’ content for the child audience, elucidate and discuss the manifestations of the gothic genre, magical realism, and other elements of the fantastic, as well as to establish a dialogue between education, history, literature, and philosophy. The epistemological basis of the dissertation is based on a hermeneutical and phenomenological interpretation of fables and fairy tales for the child audience. Thus, it was intended to establish a dialogue between education, history, literature, and the philosophy of education. The justification for this study arises from the researcher’s personal experience and professional trajectory, since fables and fairy tales have always been present. Additionally, it also emerges from the need to research human nuances based on the evolution of the historical-literary process in education, seeking both foundations for learning and pedagogical and didactic improvements.